THE IMPLEMENTATION OF DIPLOMATIC LEGAL PRINCIPLES: GERMAN EMBASSY STAFF VISITING ISLAMIC DEFENDERS FRONT (FPI) HEADQUARTERS CASE - Fradhana Putra Disantara (UNISSULA, 2021)
This legal research uses a conceptual approach and statue approach; by using primary and secondary legal materials. The purpose of this legal research is to describe the principles of diplomatic law and their application to the case of actions of German Embassy staff who have visited the headquarters of the Islamic Defenders Front (FPI). The results of this study indicate that diplomatic law is a system containing various principles of international law to regulate diplomatic relations between countries with universal approvement. Then, the development of diplomatic law is very progressive; marked by various conventions and codifications to create holistic norms. Furthermore, the actions of German Embassy staff visiting FPI headquarters cannot be justified by diplomatic law. This is because the potential acts of espionage by German Embassy staff also target the violation of the principle of non-intervention. Hence, on diplomatic law; violation of the principle of non-intervention creates persona non grata consequences.